Both D- and L-glucose polyphosphates mimic D-myo-inositol 1,4,5-trisphosphate: new synthetic agonists and partial agonists at the Ins(1,4,5)P3 receptor - Brearley, CA; Rossi, AM; Rossi, AM; Brearley, CA; Taylor, CW; Potter, BVL (American Chemical Society, 2020)
Chiral sugar derivatives are potential cyclitol surrogates in the Ca2+-mobilizing intracellular messenger D-myo-inositol 1,4,5-trisphosphate [Ins(1,4,5)P3]. Six novel polyphosphorylated analogues derived from both D- and L-glucose were synthesized. Binding to Ins(1,4,5)P3 receptors [Ins(1,4,5)P3R] and abilities to release Ca2+ from intracellular stores via type 1 Ins(1,4,5)P3Rs were investigated. β-D-Glucopyranosyl 1,3,4-trisphosphate, with similar phosphate regiochemistry and stereo-chemistry to Ins(1,4,5)P3 and α-D-glucopyranosyl 1,3,4-trisphosphate are full agonists, being equipotent and 23-fold less potent than Ins(1,4,5)P3 respectively in Ca2+-release assays, and similar to Ins(1,4,5)P3 and 15-fold weaker in binding assays. They can be viewed as truncated analogues of adenophostin A and refine structure-activity relationship understanding for this Ins(1,4,5)P3R agonist. L-Glucose-derived ligands, methyl α-L-glucopyranoside 2,3,6-trisphosphate and methyl α-L-glucopyranoside 2,4,6-trisphosphate are also active, while their corresponding D-enantiomers, methyl α-D-glucopyranoside 2,3,6-trisphosphate and methyl α-D-glucopyranoside 2,4,6-trisphosphate, are inactive. Interestingly, both L-glucose-derived ligands are partial agonists: they are amongst the least efficacious agonists of Ins(1,4,5)P3R yet identified, providing new leads for antagonist development.